Contributions to Executive Dysfunction in Operation Enduring Freedom/Operation Iraqi Freedom Veterans With Posttraumatic Stress Disorder and History of Mild Traumatic Brain Injury. Issue 2 (March 2018) - Jurick, Sarah M.; Crocker, Laura D.; Sanderson-Cimino, Mark; Keller, Amber V.; Trenova, Liljana S.; Boyd, Briana L.; Twamley, Elizabeth W.; Rodgers, Carie S.; Schiehser, Dawn M.; Aupperle, Robin L.; Jak, Amy J.
Abstract : Objective: Posttraumatic stress disorder (PTSD), history of mild traumatic brain injury (mTBI), and executive function (EF) difficulties are prevalent in Operation Enduring Freedom/Operation Iraqi Freedom (OEF/OIF) Veterans. We evaluated the contributions of injury variables, lower-order cognitive component processes (processing speed/attention), and psychological symptoms to EF. Participants: OEF/OIF Veterans ( N = 65) with PTSD and history of mTBI were administered neuropsychological tests of EF and self-report assessments of PTSD and depression. Results: Those impaired on one or more EF measures had higher PTSD and depression symptoms and lower processing speed/attention performance than those with intact performance on all EF measures. Across participants, poorer attention/processing speed performance and higher psychological symptoms were associated with worse performance on specific aspects of EF (eg, inhibition and switching) even after accounting for injury variables. Although direct relationships between EF and injury variables were equivocal, there was an interaction between measures of injury burden and processing speed/attention such that those with greater injury burden exhibited significant and positive relationships between processing speed/attention and inhibition/switching, whereas those with lower injury burden did not. Conclusion: Psychological symptoms as well as lower-order component processes of EF (attention and processing speed) contribute significantly to executive dysfunction in OEF/OIF Veterans with PTSD and history of mTBI. However, there may be equivocal relationships between injury variables and EF that warrant further study. Results provide groundwork for more fully understanding cognitive symptoms in OEF/OIF Veterans with PTSD and history of mTBI that can inform psychological and cognitive interventions in this population.